Association of PAF and its Metabolic Enzymes with GGT and the Fatty Liver Index in Healthy Volunteers - Detopoulou, Paraskevi; Nomikos, Tzortzis; Fragopoulou, Elizabeth; Antonopoulou, Smaragdi (Current Vascular Pharmacology, 2021)
Background: Platelet-activating-factor (PAF) is a lipid inflammatory mediator implicated in liver disease. Its main biosynthetic enzymes are cytidine diphosphate (CDP)-choline: 1-alkyl-2-acetyl-sn-glycerol-cholinephosphotransferase (PAF-CPT) and acetyl-coenzyme A: lyso-PAF-acetyltransferases (Lyso-PAF-AT). At the same time, PAF acetylhydrolase (PAF-AH) and lipoprotein-associated phospholipase A2 (Lp-PLA2) degrade PAF. Objective: To explore the relation of PAF metabolism with liver diseases and non-alcoholic fatty liver disease, as reflected by the fatty liver index (FLI). Methods: In 106 healthy volunteers, PAF concentration, the activity of its metabolic enzymes and gamma-glutamyl transferase (GGT) were measured in whole blood, leukocytes and serum, respectively and the FLI was calculated. Partial correlations and linear regression models were used. Results: In males, serum GGT activity was positively correlated with abdominal fat (as assessed by analysis of a manually defined region of interest in dual-energy X-ray absorptiometry), triacylglycerols, bound-PAF and Lp-PLA2, while the FLI was positively correlated with Lp-PLA2 activity. In females, serum GGT activity was negatively associated with high-density lipoprotein cholesterol (HDL-C) (age adjusted correlations, all p<0.05). Lp-PLA2 was a significant determinant of serum GGT activity in males after controlling for age, low- density lipoprotein cholesterol (LDL-C) and abdominal fat. The addition of bound-PAF in the model significantly increased the explained variance of serum GGT activity (total variance explanation 30%). Conclusion: Bound-PAF and Lp-PLA2 activity predicted serum GGT activity while Lp-PLA2 was also related to FLI. Our findings shed light on the metabolic pathways linking Lp-PLA2 to other atherosclerosis and/or oxidative markers, such as HDL-C, LDL-C, GGT and FLI and underline the important role of PAF.
Keywords: lipoprotein associated phospholipase A2 (Lp-PLA2)